2003
DOI: 10.1080/1025389032000114515
|View full text |Cite
|
Sign up to set email alerts
|

Stress Applied During Primary Immunization Affects the Secondary Humoral Immune Response in the Rat: Involvement of Opioid Peptides

Abstract: The effect of unpredictable, inescapable and uncontrollable electric tail shocks (ES) on the humoral immune response to bovine serum albumin (BSA) was investigated in the rat. Contributions of the procedures that accompany shock delivery, such as witnessing the ES procedure (stress witnessing, SW) and exposure to the apparatus for shock delivery (apparatus control, AC) to the changes in specific immunity induced by ES were also tested. All procedures were applied during primary and/or secondary immunization. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 80 publications
(86 reference statements)
0
12
0
Order By: Relevance
“…We have previously shown that exposure to electric tail shock stress (ES) profoundly suppresses the humoral immune response in rats, whereas witnessing electric tail shock administration (SW) potentiates it (Stanojević et al 2003). It is suggested that alterations in the immune response observed after stress could be specifically attributed to stress-induced changes in macrophage functions as these cells are intimately involved in the development of the humoral and cellular immune responses (Fleshner et al 1995a;Kizaki et al 1996).…”
Section: Introductionmentioning
confidence: 99%
“…We have previously shown that exposure to electric tail shock stress (ES) profoundly suppresses the humoral immune response in rats, whereas witnessing electric tail shock administration (SW) potentiates it (Stanojević et al 2003). It is suggested that alterations in the immune response observed after stress could be specifically attributed to stress-induced changes in macrophage functions as these cells are intimately involved in the development of the humoral and cellular immune responses (Fleshner et al 1995a;Kizaki et al 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Also psychogenic factors during immunization have been shown to affect the humoral immune response in stress induced animals suggesting involvement of endogenous opiate molecules [16] and stress induced IL-1beta production has been shown to have a major influence on the suppression of antibody production [17].…”
Section: Discussionmentioning
confidence: 99%
“…The humoral immune response reflects a wellcontrolled multistep homeostatic response to antigen challenge (Stanojevic et al 2003): The antibodies are responsible for neutralizing and clearing the antigen, and play a major role in the destruction of tumor cells. Studies of Id-vaccinated mice showed that anti-Id antibodies were involved in the destruction of B-cell lymphoma (Campbell et al 1988;George et al 1988).…”
Section: Discussionmentioning
confidence: 99%
“…It is of interest that Stanojevic et al (2003) demonstrated that direct exposure to an electric shock during primary immunization with BSA significantly suppressed specific anti-BSA antibody production, but shock-witnessing procedures enhanced the specific secondary humoral immune response. The shock-witnessing model involved placing the animals in the apparatus for electric shock delivery and exposing them to pheromones and vocalization from the stressed animals throughout the 5 days of testing (Stanojevic et al 2003).…”
Section: Discussionmentioning
confidence: 99%